The Morpho-Phonology-Semantics Interface in Modern Standard Arabic - Teimi, Cherif (International Journal of Language and Literary Studies, 2021)
The issue of the interface between linguistic components has got much interest in contemporary linguistics especially after the advancements that took place in the discipline of Conceptual Semantics. In essence, linguistics components have all been considered to be equal in terms of deriving meaning. In this article, the researcher scrutinized how the component of morpho-phonology interfaces with semantics. This aim was achieved through the analysis of intransitive verbs in Modern Standard Arabic (MSA, henceforth). It was found that intransitive verbs serve well in terms of demonstrating the interface between morpho-phonology and semantics. The morphological and phonological alternations of intransitive verbs result in changes in meaning. Cognition has a central role in generating causative verbs from intransitive ones.